Revisit of European-Asiatic connections in Tayloria rudolphiana (Splachnaceae, Bryophyta) based on molecular data and new morphological evidence - Yi, Yan-Jun; Xiao, Xiao-Xuan; Xu, Xiao-Xia; He, Si (Phytotaxa, 2020)
A molecular study of a rare moss, Tayloria rudolphiana has revealed a first new occurrence of this species in Central China after its first collecting more than 100 years ago from southwestern Yunnan Province. The phylogenetic analyses based on rps4 and trnL-F sequences along with its morphological features affirm the taxonomic identity of this new population, representing the latest evidence of European-Asiatic connections of this species. Photographic images detailing key morphological characters and a full description of the species are provided. The taxonomic problems of this species within China are discussed.